The Relationship between Transformational Leadership of Administrators and Quality Assurance Operations in Schools under Nakhon Sawan Primary Educational Service Area Office 3 - Khounsue, Amornrat; Naebnean, Teerapod; Dee-Aim, Kraiwit (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
The purpose of this research were to study 1) the level of transformational leadership of administrators. 2) the level of assurance operations in schools and 3) the relationship between transformational leadership of administrators and assurance operations in schools. The sample consisted of 317 administrations and teachers from used the table of Krejcie, & Morgan obtained by simple random sampling. The study instrument was a questionnaire transformational leadership of administrators with a consistency index value 0.67-1.00 and reliability at 0.99 and questionnaire assurance operations in schools with a consistency index value 0.67-1.00 and reliability at 0.98. Data were analyzed by mean, standard deviation and Pearson correlation coefficient. The research findings were as follows: 1) The level of transformational leadership of administrators in overall were at the high level. 2) The level of internal quality assurance operations in schools in overall were at the high level. and 3) The relationship between of relationship between transformational leadership of administrators and internal quality assurance operations in schools in overall there was a high level of positive correlation significance at .01 level.